2022
DOI: 10.1242/jeb.243194
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of chronic hypoxia lead to hierarchical adaptive mechanisms in goldfish metabolism

Abstract: Some hypoxia-tolerant species, such as goldfish, experience intermittent and severe hypoxia in their natural habitat causing them to develop multiple physiological adaptations. However, in fish, the metabolic impact of regular hypoxic exposure on swimming performance in normoxia is less well understood. Therefore, we experimentally tested whether chronic exposure to constant (30 days at 10% air saturation) or intermittent hypoxia (3hrs in normoxia and 21hrs in hypoxia, 5 days a week) would result in similar me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…After removing potential white muscle fibres under a binocular magnifying glass, the red muscle sample was gently dried on aluminium foil and then weighed before being placed in the respirometer chamber containing 2.1 ml of MiR05 without undergoing chemical or mechanical permeabilization. We have shown in previous studies that similar tissue preparation in fish allows for stimulation of respiratory fluxes by exogenous substrates [41,43]; we can thus assert that the plasma membranes in our experimental conditions were permeabilized.…”
Section: Methodsmentioning
confidence: 52%
See 3 more Smart Citations
“…After removing potential white muscle fibres under a binocular magnifying glass, the red muscle sample was gently dried on aluminium foil and then weighed before being placed in the respirometer chamber containing 2.1 ml of MiR05 without undergoing chemical or mechanical permeabilization. We have shown in previous studies that similar tissue preparation in fish allows for stimulation of respiratory fluxes by exogenous substrates [41,43]; we can thus assert that the plasma membranes in our experimental conditions were permeabilized.…”
Section: Methodsmentioning
confidence: 52%
“…The next morning, the U crit protocol was performed as in [41]. Individuals were exposed to a gradual increase in the current (0.5 BL/s every 30 min) until the fish was exhausted (resting on the bottom grid of the swimming area for more than 10 s; [41]). During the U crit protocol, the M˙O2 was also measured, and the MMR was calculated as the maximum oxygen consumption.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that in gibel carp, CCO activity was upregulated in both the gill and liver during hypoxia, and further elevated in the gills during recovery. Similarly, another hypoxia-tolerant cyprinid, the goldfish Carassius auratus , exhibited increased CCO activity in its muscle after short-term intermittent hypoxia exposure, which was not sustained after long-term (30 days) hypoxia ( Thoral et al, 2022 ). However, our study found that the CCO activity in the liver of gibel carp was suppressed during reoxygenation, which is in line with our previous conclusion that reoxygenation is more stressful for this species than hypoxia.…”
Section: Discussionmentioning
confidence: 99%